2016
DOI: 10.1093/femsle/fnw177
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and enzymatic response of the thermotolerant fungusFomessp. EUM1 in solid state fermentation under thermal stress

Abstract: Thermotolerance of the fungus Fomes sp. EUM1 was evaluated in solid state fermentation (SSF). This thermotolerant strain improved both hyphal invasiveness (38%) and length (17%) in adverse thermal conditions exceeding 30°C and to a maximum of 40°C. In contrast, hyphal branching decreased by 46% at 45°C. The production of cellulases over corn stover increased 1.6-fold in 30°C culture conditions, xylanases increased 2.8-fold at 40°C, while laccase production improved 2.7-fold at 35°C. Maximum production of ligno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Finally, 50 mL of 50 mM ABTS in 50 mM citrate buffer (pH 5) was added, and gels were incubated at 40 °C for approximately 20 min. to reveal the bands with laccase activity (Ordaz-Hernández et al, 2016).…”
Section: Zymogramsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 50 mL of 50 mM ABTS in 50 mM citrate buffer (pH 5) was added, and gels were incubated at 40 °C for approximately 20 min. to reveal the bands with laccase activity (Ordaz-Hernández et al, 2016).…”
Section: Zymogramsmentioning
confidence: 99%
“…The genus Fomes is capable of degrading lignin being laccases one of the enzymes responsible for this process and hence the various reports on the production of this enzyme by various species of this genus (Neifar et al, 2010;Papinutti et al, 2003;Papinutti et al, 2006;Papinutti et al, 2008;Vȇtrovský et al, 2013). Most fungal species of the genus Fomes are mesophilic, with an optimal growth temperature between 20 and 36 °C; although, a thermotolerant strain has been reported (Ordaz-Hernández et al, 2016). This strain of Fomes sp.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…When the temperature reached around 50 °C, the growth stopped and then decreased (death phase), because the fungal hyphal branching decreased at the temperature higher than 45 °C 37 . After the growth had stopped, the temperature of all beds decreased due to a decrease in heat generation from fungal respiration 38 . The decrease in glucosamine content indicated self-degradation of fungi, where the fungal cell was destroyed by many fungal self-produced enzymes, including cellulase 39 .…”
Section: Dsmentioning
confidence: 99%
“…The application of SSF technology could be an effective process for such bioconversions. Much research has shown that the properties of enzymes produced in this way exhibited higher productivity and superior performance 11, 12 . Moreover, SSF is an economical process, because agro‐industrial wastes could be used as a cheaper substrate 8, 13 .…”
Section: Introductionmentioning
confidence: 99%